ABCB1 C3435T polymorphism and the lipid-lowering response in hypercholesterolemic patients on statins: a meta-analysis. Issue 1 (December 2015) - Su, Jia; Xu, Hongyu; Yang, Jun; Yu, Qinglin; Yang, Shujun; Zhang, Jianjiang; Yao, Qi; Zhu, Yunyun; Luo, Yuan; Ji, Lindan; Zheng, Yibo; Yu, Jingbo
Abstract Background A number of researches have evaluated the association between theABCB1 polymorphism and the lipid-lowering response of statins, but the results have been inconclusive. To examine the lipid-lowering efficacy and safety associated with theABCB1 C3435T polymorphism in hypercholesterolemic patients receiving statin, all available studies were included in this meta-analysis. Methods A systematic search for eligible studies in the Cochrane library database, Scopus and PubMed was performed. Articles meeting the inclusion criteria were comprehensively reviewed, and the available data were accumulated by the meta-analysis. Results The results indicated that the comparisons of CC+CT vs. TT were associated with a significant elevation of the serum HDL-C levels after statin treatment (CC+CT vs. TT: MD, 2.46; 95 % CI, 0.36 to 4.55;P = 0.02), and theABCB1 C3435T variant in homozygotes was correlated with decreases in LDL-C (CC vs. TT: MD, 2.29; 95 % CI, 0.37 to 4.20;P = 0.02) as well as TC (CC vs. TT: MD, 3.05; 95 % CI, 0.58 to 5.53;P = 0.02) in patients treated with statin. However, we did not observe a significant association in the TG group or an association between other genetic models serum lipid parameters. In addition, statin treatment more than 5 months led to a higher risk of muscle toxicity. Conclusions The evidence from the meta-analysis demonstrated that theABCB1 C3435T polymorphism may represent a pharmacogenomic biomarker for predicting treatment outcomes in patients on statins and that statin treatment for more than 5 months can increase the risk of myopathy.